Recycling of white lupine meal using solid-phase microbiological fermentation - Olga A. Mironova; Anatoly A. Kirichuk; Anton P. Karmazin; Lyudmila P. Mironova (RUDN Journal of Ecology and Life Safety)
The protein content in white lupine seeds is 35-38%, so it is considered as an alternative to soybeans. After separating the oil from the lupine seeds, the meal remains. Lupine meal is a waste product of lupine oil production. An environmentally friendly method of lupine meal utilization by solid-phase microbiological fermentation is proposed with the prospect of using the fermented product for animal feed. The results of laboratory studies of white lupine meal fermented using Lesnov’s starter have proven that, regardless of the fermentation time, the physicochemical properties of the resulting product are significantly improved in comparison with the native substrate; the obtained fermented product meets the requirements of biological and chemical safety for animal feed.